Development of Android-based Learning to Improve Computational Thinking Skills in Junior High School - Zafrullah Zafrullah; Slamet Suyanto; Astri Wahyuni; Rizki Tika Ayuni; Fini Rezy Enabela Novilanti (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2023)
In this modern era, it is important for teachers to use Android as a learning medium. This aims to facilitate the learning process. The purpose of this study was to test the validity, practicality, and effectiveness of Android-assisted learning media to improve junior high school students' thinking skills. This study used the ADDIE model with 30 students of Rengat 1 Public Middle School as research subjects. The instruments used are non-test instruments in the form of validation sheets and practicality sheets. For data collection techniques, namely by taking validation data, practicality data and effectiveness to students. The data analysis technique used is to conduct product validation tests on experts, practicality and effectiveness tests on students. From the research results, it was found that the media was already in very valid results with a percentage of 88.25%, and for practical results a percentage of 80.26% was obtained with a very practical category. The effectiveness results showed that the pretest results of students who achieved KKM were only 20%, and the posttest of students who achieved KKM increased by 80%. This makes the learning media ready to be used by the teacher to students in the classroom.